HUBUNGAN INISIASI MENYUSU DINI (IMD) TERHADAP LAMANYA PELEPASAN PLASENTA PADA KALA III PERSALINAN DI RUMAH SAKIT ISLAM AR RASYID PALEMBANG - Purnama Dewi, Bela; Handayani, Mutmainah; Alfhyna J.R, Rinka; Arlina, Zakinah (Jurnal Kesehatan dan Pembangunan, 2025)
According to 2021 Basic Health Research (RISKESDAS) data, 52.5 percent or only half of the 2.3 million babies aged less than six months are exclusively breastfed in Indonesia, or a decrease of 12 percent from the figure in 2019. Early breastfeeding initiation rate ( IMD) also decreased from 58.2 percent in 2019 to 48.6 percent in 2021. The aim of this research was to determine the relationship between early initiation of breastfeeding and the length of expulsion of the placenta in the third stage of labor at the Ar Rasyid Islamic Hospital in Palembang. This research uses survey research with a cross sectional approach design. The sampling technique used was purposive sampling, namely using a random method. Analysis uses the Chi-square statistical test. The total sample of researchers was 79 respondents. Based on the research results, it was found that 75 (94.9%) of those who carried out Early Breastfeeding Initiation (IMD) and the duration of normal placental expulsion was ? 15 minutes were 76 (96.2%), that there was a significant relationship between Early Breastfeeding Initiation and Duration. Expulsion of the Placenta in the Third Stage of Labor with a value (p-value = 0.006). It is recommended that hospitals always carry out Early Breastfeeding Initiation (IMD) to reduce the risk of bleeding.